2020
DOI: 10.15252/emmm.201911793
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of interferon signaling by fibroblast growth factors promotes viral replication

Abstract: Fibroblast growth factors (FGFs) play key roles in the pathogenesis of different human diseases, but the cross‐talk between FGFs and other cytokines remains largely unexplored. We identified an unexpected antagonistic effect of FGFs on the interferon (IFN) signaling pathway. Genetic or pharmacological inhibition of FGF receptor signaling in keratinocytes promoted the expression of interferon‐stimulated genes (ISG) and proteins in vitro and in vivo. Conversely, FGF7 or FGF10 treatment of keratinocytes suppresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 59 publications
(80 reference statements)
1
14
0
Order By: Relevance
“…The molecular mechanism underlying how club cell-driven FGF9 overexpression might promote a type I IFN signature upon infection remains unclear. Within the current literature, FGFs commonly inhibit or suppress the functions of IFNs in both disease and development contexts [ 38 40 ]. Recently, multiple studies have demonstrated that FGF-driven antagonism of IFN signaling can promote viral pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanism underlying how club cell-driven FGF9 overexpression might promote a type I IFN signature upon infection remains unclear. Within the current literature, FGFs commonly inhibit or suppress the functions of IFNs in both disease and development contexts [ 38 40 ]. Recently, multiple studies have demonstrated that FGF-driven antagonism of IFN signaling can promote viral pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, multiple studies have demonstrated that FGF-driven antagonism of IFN signaling can promote viral pathogenesis. For example, FGF7 treatment of keratinocytes enhanced herpes simplex virus-1, lymphochoriomeningitis virus, and Zika virus infection by inhibiting ISG expression [ 40 ]. Additionally, Zika virus infection of human fetal astrocytes elevated expression of FGF2, which suppressed IFN signaling and facilitated Zika virus infection and spread [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration that EGF and FGF2 help retain FOXG1 nuclear localization following ZIKV infection, and that ZIKV induces FGF2 expression supports the combinatorial or dose-dependent role of GFs in forebrain shaping, the pathophysiological relevance of FGF2, and suggests a further role of GFs in ZIKV spread. In this context, recent reports also show that ZIKV induces FGF2 expression and FGF2 facilitates virus replication and cell-to-cell spread ( Limonta et al., 2019 ); moreover, in ZIKV-infected pregnant women, blood concentration of FGF2 correlates with the severity of the affected fetuses ( Kam et al., 2017 ) and, finally, FGF2 receptor inhibitors have been suggested as a promising approach for antiviral therapies ( Carlin, 2022 ; Langford et al., 2005 ; Maddaluno et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, multiple studies have demonstrated that FGF-driven antagonism of IFN signaling can promote viral pathogenesis. For example, FGF7 treatment of keratinocytes enhanced herpes simplex virus-1, lymphochoriomeningitis virus, and Zika virus infection by inhibiting ISG expression 41 . Additionally, Zika virus infection of human fetal astrocytes elevated expression of FGF2, which suppressed IFN signaling and facilitated Zika virus infection and spread 42 .…”
Section: Discussionmentioning
confidence: 99%